2019
DOI: 10.1017/s0007114519003015
|View full text |Cite
|
Sign up to set email alerts
|

Intra-individual and inter-individual variations in iodine intake and excretion in adult women: implications for sampling

Abstract: Iodine intake and excretion vary widely; however, these variations remain a large source of geometric uncertainty. The present study aims to analyse variations in iodine intake and excretion and provide implications for sampling in studies of individuals or populations. Twenty-four healthy women volunteers were recruited for a 12-d sampling period during the 4-week experiment. The duplicate-portion technique was used to measure iodine intake, while 24-h urine was collected to estimate iodine excretion. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…To my knowledge, there are no studies that have extensively compared the difference in intra-and inter-individual variation of UIC between iodine-deficient and -sufficient individuals or populations. For example, the range of inter-individual 24-h UIC variation for iodine-deficient and -sufficient individuals in the study was 29-64 % and 46-69 %, respectively, which were not discussed by the authors (1) . This is particularly important if we are planning to further consider the usefulness of UIC in the determination of recent iodine status in individuals.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…To my knowledge, there are no studies that have extensively compared the difference in intra-and inter-individual variation of UIC between iodine-deficient and -sufficient individuals or populations. For example, the range of inter-individual 24-h UIC variation for iodine-deficient and -sufficient individuals in the study was 29-64 % and 46-69 %, respectively, which were not discussed by the authors (1) . This is particularly important if we are planning to further consider the usefulness of UIC in the determination of recent iodine status in individuals.…”
mentioning
confidence: 71%
“…The authors addressed a very important issue in the assessment of iodine status using urinary iodine concentration (UIC). They reported that the mean intra-individual variation was lower than the mean inter-individual variation for 24-h urinary iodine excretion, 24-h UIC and iodine intake (48, 55 and 63 % v. 24, 32 and 14 %, respectively) in a group of participants who were given prescribed diets for 12 d during the 4-week study (1) . Although UIC can be used to reflect recent iodine status of a population, there is high intra-and interindividual variation between-and within-individuals, which further increases UIC distribution spread (2,3) .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…We did not identify any differences in iodine status associated with egg consumption but in NDNS this is estimated from urinary iodine concentration in spot samples, which has well‐recognised methodological limitations (The Scientific Advisory Committee on Nutrition 2014; Chen et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
“…When a steady state is present, iodine in urine is regarded as a measure used to estimate bioavailable iodine in the diet. Iodine clearance studies using intravenously or orally ingested radioiodine have been reported; however, information on the short-term change of urinary iodine excretion (UIE) from ingested meals is limited [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In addition, dietary iodine intake (DII) in individuals is highly variable and the range can vary by more than two orders of magnitude depending on the food choices for that day since iodine tends to be concentrated in certain foods.…”
mentioning
confidence: 99%